FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KERUPUK OLAHAN UDANG HASIL INDUSTRI RUMAH TANGGA DI KABUPATEN TANJUNG JABUNG BARAT (STUDI KASUS KECAMATAN TUNGKAL ILIR KAMPUNG NELAYAN) - Afriyeni, Amalia (e-Journal Perdagangan Industri dan Moneter, 2015)
The aim of this study, first to determine the socio-economic conditions of processed prawn crackers businessman educational level, a number ofdependents, income, price, production. Second to know and analyze the factors that influence the production of processed prawn crackers. The data used in this study was primary data in the form of the figures used by the industry of processed prawn crackers in KampungNelayan. Then thesecondary data obtained from related institutions. Then the data is analyzed using descriptive and quantitative methods. The results obtained from this study can be known that socio-economic conditions of the respondents viewed from the level of education on average still graduate primary school with an average number of dependents 2 children, and obtained by craftsmen of processed prawn crackers is around Rp. 4,320,000 a price of crackers Rp. 50,000 per kg and can produce up to 136 Kg per month. From the results of regression testing, variable labor (0.0145) and raw materials (0.0008) significantly affects the production of processed prawn crackers, this can be seen in thitung>ttable at 95% confidence level (Î± = 0.05). And the results obtained a regression coefficient of determination (R) of 0.887857.